Effectiveness of Regional Retribution Revenue and Its Contribution to Local Own-Source Revenue in Southwest Maluku Regency - Killay, Thimotina; Leunupun, Engrith Grafelia; Kaary, Gilbert Robert (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Regional retributions are one of the most significant sources of Local Own-Source Revenue (PAD), serving as an indicator of a region’s fiscal independence. In Indonesia, many local governments, including the Maluku Barat Daya Regency, still rely heavily on central government transfers, making the optimization of PAD through effective retribution management crucial. This study aims to analyze the effectiveness and contribution of regional retribution to the Local Own-Source Revenue (PAD) of the Maluku Barat Daya Regency during the period 2017–2021. The research employs a descriptive quantitative method. The data used are secondary data obtained from the Regional Revenue Agency (BAPENDA), specifically from the realization reports of the regional budget (APBD). The results indicate that the effectiveness of regional retribution revenue fluctuated throughout the observed period and has not yet reached the targeted level. Some types of retributions, such as public service retributions and certain licensing retributions, showed relatively high effectiveness in the early years but declined significantly during 2020–2021. Meanwhile, the contribution of regional retribution to PAD remained low and showed no significant growth over the five-year period. Overall, regional retribution has not made a substantial contribution to the local revenue of Maluku Barat Daya Regency. Therefore, it is necessary to enhance the effectiveness of collection, supervision, and taxpayer awareness, as well as to implement digital systems to strengthen regional fiscal independence. The findings of this study support the stewardship theory, emphasizing the government’s responsibility to manage public revenues transparently, efficiently, and accountably.